Effects of a painful stimulus on stress regulation in male patients with borderline personality disorder: a pilot study - Naoum, Janina; Kleindienst, Nikolaus; Baumgärtner, Ulf; Willis, Franziska; Mancke, Falk; Treede, Rolf-Detlef; Bohus, Martin; Schmahl, Christian (Journal of personality disorders, 2019)
Pain processing in relation to stress has so far not been investigated in male patients with borderline personality disorder (BPD). This experimental pilot study examined 17 male BPD patients and 20 male healthy controls (HCs) to assess the effects of a pain stimulus on arousal, aggression, pain (ratings), and heart rate. At baseline, BPD patients showed significantly higher arousal and aggression; however, there was no significant difference in heart rate compared to the HC group. Following stress induction, a noninvasive mechanical pain stimulus was applied. No significant differences in pain ratings or heart rates were found between the groups. For arousal, a significantly stronger decrease was revealed in the BPD group compared to the HC group (t = 2.16, p = .038). Concerning aggression, the BPD group showed a significantly greater decrease after the pain stimulus than the HC group (t = 3.25, p = .002). This data showed that nonsuicidal self-injury can reduce arousal and aggression in male BPD.